The influence of business profiles on brand equity awareness among small and medium scale food entrepreneurs in Terengganu - Zakaria, Zainuddin; Jusoff, Kamaruzaman; Abdul Halim, Muhammad Abi Sofian; Wan Abdul Aziz, Wan Asri (Institute of Interdisciplinary Business Research, 2009)
The state government of Terengganu, Malaysia is encouraging small scale entrepreneurs to get involve in the promotion, packaging, labeling and branding of their products. However, the number of entrepreneurs in the state who are presently involved in branding is still small. A survey was conducted using questionnaire in order to discover the influence of the entrepreneurs' business profiles on their knowledge, awareness and involvement towards brand equity. Six elements of business profiles have been identified which include Size of Business, Type of Ownership, Types of Products Sold, Source of Funding, Business Zone and Market Size. These entrepreneurs are registered under Yayasan Pembangunan Usahawan Terengganu (YPUT) and involved in the production or selling of food products in the state. Statistical analysis such as the Chi Square and Cramer's V were used to determine the relationship between the entrepreneurs' level of brand equity awareness with their business profile. Result shows that the entrepreneurs' business profiles were found to have significant and moderately strong relationships with their level of brand equity awareness. Future researchers would benefit from this study and use it as a platform to further investigate other factors such as organizational culture, government support and style of management in influencing the entrepreneurs' knowledge, awareness and involvement in branding.